Factors Affecting Response to Anakinra in Crystalline Arthritis Flares. Issue 4 (31st March 2022) - Ahmed, Hamdy Mohamed Abdelaziz; Sun, Dongmei; Gaffo, Angelo
Abstract : Background: Interleukin 1 inhibition with anakinra has shown efficacy in the management of crystalline-induced arthritis (CIA) flares. Gout treatment guidelines recommend its use after contraindication or intolerance to first-line therapies. The aim of this study is to identify features associated with better response to anakinra when used to treat CIA flares. Methods: This is a medical record review study that included inpatients with acute CIA in whom anakinra was used between the years 2014 and 2019 at one tertiary center (University of Alabama at Birmingham). The primary end point was response to anakinra treatment defined as a decrease in the reported visual analog score of at least 50% within 48 hours of initiation of treatment. Demographic, clinical, and laboratory factors were compared, and factors found significant in bivariate analysis at a p value of less than 0.15 were tested in a multivariate logistic regression analysis for independent association with the response. Results: A total of 55 admission encounters were analyzed. The mean age was 60.1 years, 36 (66%) were men, and 31 (56%) were African Americans. Twenty-eight of 49 (57%) met the primary end point of response at 48 hours, but 52 of 55 (94.5%) ultimately responded to anakinra during hospital stay. Factors associated with response at 48 hours were race, reason for admission related to cardiac etiologies, not having failed steroids before trial of anakinra, and hospital admission within 48 hours of initiation of flare. On a multivariable logistic regression model, we could not find significant independent associations with response to anakinra. Conclusions: Our study showed high response rates to anakinra. We could not identify factors associated with a more robust, early response. It is likely that anakinra is equally effective across a wide range of clinical scenarios.